Lipase Activity of Mucor pusillus - Somkuti, G. A. (1968)
Two strains of Mucor pusillus were examined for their ability to synthesize lipase in a complex medium used in the production of milk-clotting protease. Lipase activity of both strains reached maximal after 6 days of incubation under submerged conditions at 35 C. Lipase secreted into the medium hydrolyzed butterfat and vegetable lipids, as well as selected synthetic triglycerides. About 50% of lipase activity was destroyed after a 45-min heat treatment at 58 C.